INTEGRATION OF ISLAMIC VALUES INTO THE FINANCIAL EDUCATION CURRICULUM: A STUDY OF ISLAMIC EDUCATIONAL INSTITUTIONS IN INDONESIA - Luthfiah Al Asbin Ulyani; M. Ali Akbar (Yayasan Amanah Nur Aman, 2026)
This study aims to examine the integration of Islamic values into financial education curricula at Islamic educational institutions in Indonesia. Financial education based on Islamic values is a fundamental need for developing a Muslim generation that possesses both financial competence and strong moral integrity. Using a library research method, this study collects, analyzes, and synthesizes relevant scholarly literature, including books, journals, academic articles, and educational policy documents published between 2020 and 2025. The review findings indicate that integrating Islamic values such as amanah (trustworthiness), justice, maslahah (public interest), and the prohibition of riba (usury) into financial education curricula enhances Islamic financial literacy and fosters responsible economic behavior. Islamic educational institutions, including pesantren, madrasahs, and Islamic higher education institutions, have substantial potential to implement sharia-based financial education. Nevertheless, challenges remain in curriculum standardization, teacher competence, and the availability of integrated teaching materials. This study recommends developing an integrated curriculum that comprehensively combines modern financial literacy with Islamic economic principles.